ANALYSIS OF PROPERTIES OF DECORATIVE CONCRETE IN ISOPARAMETRIC CONDITIONS OF OPTIMALITY CRITERIA (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The article presents two computer materials science methods for analyzing the functional properties of decorative concrete. The method of experimental-statistical modeling is used to build nonlinear structured models that describe the material's physical, mechanical, and technological properties in the coordinates of five factors of concrete composition. The study of the influence of recipe factors on the characteristics of the composite was carried out according to a symmetrical three-level 27-point plan. Depending on the nature of the effect on the decorative composite, varied raw materials are combined into two groups of factors ‒ modifications of the cement-sand system and parameters of dispersed reinforcement. A comparative analysis of the local properties fields of reinforced and non-reinforced material compositions showed the feasibility of reinforcing the cement-sand matrix with hybrid glass fibers. However, based on the purpose of the work – to control the characteristics of a decorative non-reinforced composite, subject to a constant level of one of its criteria, the method of isoparametric analysis was used. The change in the quality criteria of composite compositions was analyzed in two versions of isoparameters. In the first one, all mortar mixes were characterized by the same viability within time t = 1.0±Dt, in the second one, all concrete compositions were isosthenic within the limits of compressive strength fcm = 56±Dfcm. For statistical testing of the characteristics of the material, together with experimental statistical models, the Monte Carlo method was used. According to the results of the isoparametric analysis of the functional properties of the decorative composite, it was fairly reliably determined by the area of compromise relationships between the zeolite and the fine-grained filler, however, the coordinates of their optimal amount don’t match according to all criteria. An analysis of the results obtained by this method demonstrates that an engineering compromise between these factors should be sought in the area of their main levels of variation. Introducing finely dispersed zeolite instead of a part of cement is a technologically useful technique for improving the quality and durability of unreinforced decorative concrete.
Keywords: decorative concrete; zeolite; fibre; experimental-statistical model; strength; computational experiment; constant level of property; isoparametric analysis.